Anti-COVID19 Vaccine among Workers at the Local Health Authority of Rieti (Italy). Study on the Vaccine Efficacy and Seroprevalence Post-Vaccination - Luca A, De; L, Provvidenti; O, Giancola; G, Banchieri; B, Sed; Giorgio F, De; S, Venarubea; M, Angelucci; M, D’Innocenzo (Journal of Public Health International, 2022)
Objectives Our study aims to determine the trend of the antibody titer and assess the efficacy of the vaccine. Methods It was conducted on 983 healthcare professionals between 27 February 2020 and 22 October 2021 at the Local Health Authority (ASL) of Rieti. Workers voluntarily underwent serological testing before vaccination (T1), at least 15 days after vaccination (T2), and at least 150 days after vaccination (T3). We picked individuals who had received two doses of the vaccine. As for positivity, we assessed incidence – and therefore symptomatology – in three time intervals. We used a contingency tables for the analysis and tested the relation to the chi-square test and ANOVA test. Regarding differentials in terms of antibody capacity, we considered different time intervals: the methodological approach was the same. Results The average value of the dimeric serological testing at T1 was equal to 28.80 AU/mL, which increased to 220.55 AU/mL at T2, and then decreased to 143.62 AU/mL at T3 (P = 0.000). At T2, the number of people with a protective titer was equal to 95.96% of the total; at T3, it was equal to 96.39% (P = 0.019). Before the vaccination campaign, 75 workers tested positive (25 paucisymptoms, 4 severe symptoms). After vaccination, 14 workers tested positive: almost all were asymptomatic. Conclusion Vaccination determines a statistically significant variation of the average value of antibody titer, a statistically significant reduction of positive swab tests and a better prognosis.
Keywords: Immunology; Epidemiology; virology; pathology; pathogenicity